Comparative Evaluation of Periodontal Parameters and Microbiological Profile in Smokers and Non-Smokers - Zeeshan Danish; Mahirah Iqbal; Irfan Salim; Taif Ahmad; Abira Hamid; Hina Tariq (Journal of Gandhara Medical and Dental Sciences)
OBJECTIVES